PENERAPAN E-LEARNING UNTUK MENDUKUNG PENINGKATAN KOMPETENSI PAMONG BELAJAR - Muktiono Waspodo (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2010)
Learning civil competency improvement is needed in order to support implementation of the basic task. Educators on Learning as a civil nonformaJ channels also need to learn. This requires a systematic and continuous efforts to innovate learning for Civil Education. one of them is by using e-learning programs for the improvement of civil competence study. Need to be prepared carefully to develop e-learning, that can be utilized by the Civil Learning.